Analisis Pengaruh Harga Produk Dan Promosi Terhadap Kepuasan Pengguna Sepeda Motor Matic Vario Pada CV. Semoga Jaya Di Tenggarong. - Suhartono, Hedi (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2008)
The regression equality that is resulted as follows Y = 3,198 + 0,325X1 + 0,153X2 + 0,222X3. Fromthe result of equality can be defined contanta (a) as 3,198 tells if X1, X2, X3 equals zero thenconsumers satisfaction by 3,198. From F test,has obtained F count is 50, 982 meanwhile F tablevalue resulted value as 2,48.This case means that F count > F table or 50, 982 > 2,48 so that can besaid cost variable, product and promotion is equals in showing their effects to the consumerssatisfaction. R value is 0,817,it means the correlation among cost, product and promotion and thesatisfaction of consumers is very strong. R square value is 0,668,it means that 66,8% degree ofconsumers satisfaction can be explained or affected by cost variable, product and promotion, as forthe rest 33,2% degree of consumers satisfaction is affected by other factors out of thisresearch.According to explanation above, so can be concluded that the first hyphothesis which statesthat cost variable, product and promotion give positive effect to the satisfaction of the users of Variomatic motorcycle at CV. Semoga jaya in tenggarong.